A new species of columnea (gesneriaceae) from the cordillera oriental of colombia (2010)
A new species of Columnea belonging to section Collandra (Gesneriaceae) is described and illustrated. The species is found in the Eastern Andes of Colombia (CordilleraOriental), in the Departamento of Santander.